Exploring the challenges facing women entrepreneurs in informal cross-border trade in Botswana. Issue 8 (29th October 2014) - O. Ama, Njoku; T. Mangadi, Kagiso; A. Ama, Helen
Abstract : Purpose: – This paper aims to look at Botswana women entrepreneurs involved in informal cross-border trade (ICBT). It addresses the following questions: What is the nature of the entrepreneurship activities that the women engage in, the funding sources and profitability of the businesses? How has the business helped to enhance women's economic empowerment? What are the factors that influence participation of women in these businesses and their challenges? Design/methodology/approach: – The study used both qualitative and quantitative methods in studying the challenges faced by Botswana women entrepreneurs in ICBT. A sample of 319 women were identified for study using a combination of the systematic sampling method and snowball techniques. Questionnaires were administered on the sampled women by trained research assistants. In addition, key informant interviews and focus group discussion were conducted on selected women entrepreneurs and key personnel from the Ministry of Trade and Industry, Customs and Immigration Offices at the border posts. Findings: – The study revealed that the majority of the women (67 per cent) were under 35 years of age, 69 per cent had very little education (senior secondary certificate and below), 41 per cent were unemployed and 44 per cent were single (never married). The women traded mainly in agricultural products and industrial goods. Raising income for the families (49 per cent) ranked highest as the push factor for the women entrepreneurs. The average monthly profit made by the women was P5916.77 ± 409.86 (US657.42 ± 45.54). The major constraints faced by the women traders were delays at the borders, long hours of travel, time away from their homes and stiff completion with other traders. ICBT was shown to be highly profitable for the women entrepreneurs, with gross profit margin on imported goods at 59.5 per cent. Research limitations/implications: – The study limitations included fear that the research assistants are agents of the income tax department disguised as researchers and that the collected information may be passed on to government authorities for the purpose of taxation. It was not possible to evaluate the impact of these feelings by the respondents on the responses. However, "anonymity" was the best strategy for getting information. They were assured in the consent form and orally that information provided was not going to be divulged to any other sources and that the questionnaire does not contain anybody's personal information which could be used to track the person. Notwithstanding these limitations, the study design was appropriate for the purpose of the research. The instrument was adequate as can be seen from the high values of the Cronbach's alpha coefficient (0.90) and knowledgeable research assistants who collected the data under the supervision of the authors. Practical implications: – The women entrepreneurs were able to generate substantial incomes and profits that enabled them to improve the livelihood of the families and empowered them to themselves take major decisions in their families. The educational status of the women needs to be improved, as this will be necessary to improve their entrepreneurial skills. Social implications: – Reduction in internal taxes on imported goods by the women can enhance the profitability of the businesses. Originality/value: – The study is highly original, especially as no such study has been undertaken in Botswana before. The methodology used is very adequate and specially articulated to achieve the objective of the study. The research assistants were well-trained for this assignment.